Aggressiveness in Driving: A View From the Spanish Drivers' Perception. - Alonso, Francisco; Esteban, Cristina; Serge, Andrea; Faus, Mireia (Violence & Victims, 2024)
Aggressiveness is a concerning issue due to its contribution to road crashes. This study aims to provide an overview on how Spanish drivers perceive aggressive driving, analyzing how this perception is linked to sociodemographic features. Thus, a cross-sectional study was designed, where 1,079 Spanish drivers took part in a telephone survey on aggressiveness' importance, influence on traffic accidents, and frequency of performance. For data processing, Exploratory Data Analysis and Unifactorial Variance Analysis were conducted. The results showed that the perception of aggressive driving has a high valuation and a high-perceived risk, with differences for sex, age, and driving experience. The findings suggest that some groups perceive more aggressiveness than others, meaning it is necessary to develop measures to reduce biases through a gender perspective.